Natural sucrose esters: Perspectives on the chemical and physiological use of an under investigated chemical class of compounds - Mora Vargas, Jorge Andrés [UNESP]; Orduña Ortega, Julieth [UNESP]; Metzker, Gustavo [UNESP]; Larrahondo, Jesus Eliecer; Boscolo, Mauricio [UNESP] (Elsevier, 2020)
The present review describes the chemistry and physiological properties of the sucrose esters (SEs) obtained from natural or synthetic pathways, with emphasis on those that have aliphatic and phenylpropanoid substituents on their sucrose moiety. Synthesis, extraction and characterization methods for the SEs and NSEs are discussed in terms of synthetic procedures, separation techniques and spectroscopic methods. The physiological properties are discussed taking into account the nature of the substituent groups and their regiochemistry (position and number of substitutions) on the sucrose moiety.
Keywords: Aliphatic substituents; Natural sucrose esters (NSEs); Phenylpropanoid substituents; Physiological activity; Sucrose esters (SEs)